Your mother was a Neanderthal - Scieszka, Jon.; Smith, Lane (New York, N.Y. : Penguin Group, 1995)
The Time Warp Trio find themselves in the middle of an adventure in prehistoric times, where cave art is a form of graffiti and "rock" music takes on a whole new meaning.
"Puffin books."
610
Accelerated Reader AR
Keywords: Time Warp Trio (Fictitious characters) -- Fiction; Time travel -- Fiction; Prehistoric peoples -- Fiction; Humorous stories